Auditor Performance Determinants: The Moderating Role of Organizational Culture in Indonesia’s Big Ten Accounting Firms - Dharma, Ida Bagus Surya; Baridwan, Zaki; Atmini, Sari (International Journal of Social Science and Business, 2025)
This study investigates the influence of professionalism, independence, work motivation, and self-efficacy on auditor performance, with organizational culture as a moderating variable. Grounded in attribution theory, which explains behavior through internal and external factors, the research focuses on auditors from Indonesia’s Big Ten public accounting firms. Using a quantitative explanatory approach, data were collected through a structured questionnaire distributed via purposive sampling to 202 respondents. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The findings of this study revealed that independence, work motivation, and self-efficacy positively influenced auditor performance, while professionalism had no effect. Additionally, organizational culture only moderated the relationship between motivation and performance, but not for professionalism, independence, or self-efficacy. The study offers theoretical, practical, and policy implications. Theoretically, it supports attribution theory by confirming that internal factors such as motivation, self-efficacy, and independence influence auditor performance, with their effects shaped by organizational culture. The limited impact of professionalism suggests a need for structural support to actualize professional values. Practically, audit firms should strengthen these competencies through mentoring, training, and ethical safeguards, supported by a collaborative culture. At the policy level, Indonesia Chartered Accountants and Indonesian Institute of Certified Public Accountants are encouraged to embed behavioral competencies into certification and promote culture-based performance systems in public accounting firms.